Dependence on zopiclone: a case report - Guo, Nana; Zhou, Xuhui (Frontiers in Psychiatry, 2025)
BackgroundZopiclone, a cyclopyrrolone derivative, is commonly employed for the short-term treatment of different types of insomnia. In comparison to benzodiazepines, Zopiclone appears to have a lower risk of abuse potential and withdrawal symptoms. Nevertheless, as the use of Zopiclone has increased, reports of abuse and dependence have begun to surface in the literature.Case presentationThis case report describes a 43-year-old male patient who has been taking zopiclone for 12 years, with a maximum daily dose of 112.5 mg. Two days after discontinuing the medication, the patient experienced withdrawal symptoms such as palpitations, sweating, irritability, hallucinations, and impulsive behavior, which resulted in his admission to a psychiatric hospital. After 17 days of treatment with diazepam, quetiapine fumarate, magnesium valproate, and trazodone hydrochloride, the patient’s withdrawal symptoms alleviated, sleep quality improved, and medication cravings decreased.ConclusionSimilar to benzodiazepines, Zopiclone may also result in abuse and dependency issues. Therefore, when prescribing Zopiclone, physicians must be fully aware of it.